Supporting the midwifery workforce: An evaluation of an undergraduate midwifery student employment model at a large tertiary maternity service in Victoria, Australia. Issue 1 (February 2023) - Mumford, Sharon; Newton, Michelle; Benzie, Charlie; Forster, Della; Matthews, Robyn; Hyde, Rebecca; Llewelyn, Fleur; McLachlan, Helen
Abstract: Background: In 2020, in response to major maternity workforce challenges exacerbated by the COVID-19 pandemic, the Victorian Department of Health implemented a number of workforce maximisation strategies, one of which was employment of undergraduate midwifery students called 'Registered Undergraduate Student Of Midwifery' (RUSOM). Aim: To evaluate the RUSOM model implemented in a tertiary maternity service in Melbourne, Australia. Methods: A cross-sectional online survey was distributed to all RUSOMs and midwives at the study site in August 2021. Findings: Twenty of 26 RUSOMs (77%) and 110 of 338 permanent midwives (33%) responded. Both groups considered the model to be a positive workforce strategy that contributed to work readiness of students, and increased confidence and competence to practise. RUSOMS and midwives reported positives for the organisation including improving workload for midwives on the postnatal ward, enhancing quality of care and outcomes for women and babies, and the value of RUSOMs as team members. RUSOMs felt well supported, supervised and clinically and theoretically prepared. Both groups considered RUSOMs were underutilised, and that they could undertake additional duties, and both thought that the RUSOM model should continue. Conclusion: The model was highly valued by both RUSOMs and midwives. There was strong agreement that the model should continue and that the list of duties could be expanded. Given these findings, further research should explore the expansion and sustainability of RUSOMs in the maternity workforce.